CLINICAL-NEUROPHYSIOLOGICAL AND NEUROIMMUNOLOGICAL CHARACTERISTICS OF CHRONIC HEADACHE FORMS - Akhmedova Dilafruz Bahodirovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract Chronic headache disorders, notably chronic migraine and tension-type headaches, represent a growing neurological concern due to their refractory nature and multidimensional pathophysiology. This research, grounded on a cohort of 315 patients, explores the interplay of neurophysiological and neuroimmunological factors, analyzing EEG markers, heart rate variability (HRV), and cytokine levels including IL- 6, TNF-α, and IL-10. Our findings demonstrate distinct EEG profiles and elevated inflammatory markers in chronic migraine cases, supporting the hypothesis of central sensitization and immune dysregulation. Treatment optimization through multimodal approaches, tailored to patients’ neurobiological and psychological profiles, yielded significant reductions in attack frequency and improved quality of life.